Analysis of the Cochrane Review: Antihistamines for the Common Cold. Cochrane Database Syst Rev. 2015;11:CD009345. - Sterrantino, Carmel (2016)
The common cold is an acute, self-limiting inflammation of the mucosa of the upper airways, which may involve one or all the sinuses, nasopharynx, oropharynx and larynx. It is common to have at least one episode per year. Common cold symptoms, which may include sore throat, sneezing, nasal congestion, runny nose, headache, malaise and mild fever usually disappear within a few days without treatment. The causative agent of most colds is rhinovirus. Although not associated with mortality, common cold is associated with significant morbidity. There is no vaccine or cure for common cold and, therefore, their treatment is centered on relieving the symptoms. This Cochrane review aimed to synthesize the existing evidence about the clinical benefit of antihistamines, used as monotherapy, compared with placebo or no treatment in children and adult patients with common cold. A total of 18 randomized clinical trials with 4342 participants were included. Main results were: 1) Antihistamines have a small (days one and two) beneficial effect in the short term on the severity of overall symptoms in adult patients, although this effect is not present in the medium to long term; 2) antihistamines were not associated with a clinically significant beneficial effect on the individual symptoms (nasal congestion, rhinorrhea, and sneezing); 3) Antihistamines are not associated with an increased risk of adverse effects; 4) No conclusion can be made about the effectiveness of antihistamines in pediatric populations. Our interpretation of the results is that the available evidence is insufficient to support the prescription or buying OTC antihistamines to relieve the symptoms of common cold without allergic component.